Asymmetric synthesis of chiral oxindoles using isatin as starting material. Issue 13 (29th March 2018) - Mohammadi Ziarani, Ghodsi; Moradi, Razieh; Lashgari, Negar
Abstract: Asymmetric synthesis plays an important role in the synthesis of therapeutics and natural products. Asymmetric oxindoles with a stereogenic quaternary carbon center are extensively present in various natural products and biologically active compounds. Several methods such as employing chiral auxiliaries or chiral catalysts were developed for asymmetric synthesis of spirooxindoles or 3, 3-disubtituted oxindoles. In this review, we make a detailed overview of the latest developments in the use of isatin as starting material for the asymmetric synthesis of spirooxindoles and 3, 3-disubstituted oxindoles during the period from 2015 to 2017. Graphical abstract: